The ever-changing past : why all history is revisionist history - Banner, James M., Jr., 1935- (New Haven ; London : Yale University Press, 2021)
"History is not, and has never been, inert, certain, merely factual, and beyond reinterpretation. Taking readers from Thucydides to the origin of the French Revolution to the Civil War and beyond, James M. Banner, Jr. explores what historians do and why they do it. Banner shows why historical knowledge is unlikely ever to be unchanging, why history as a branch of knowledge is always a search for meaning and a constant source of argument, and why history is so essential to individuals' awareness of their location in the world and to every group and nation's sense of identity and destiny. He explains why all historians are revisionists while they seek to more fully understand the past, and how they always bring their distinct minds, dispositions, perspectives, and purposes to bear on the subjects they study."--
Revisions without end: the origins of the American Civil War -- The ancient origins of revisionist history -- Revisionist history in the modern era -- Varieties of revisionist history -- Some fruits of revisionist history -- History and objectivity.
Includes bibliographical references and index.
James M. Banner, Jr. is the author of many books, including The Elements of Teaching. Most recently, he is editor of Presidential Misconduct: From George Washington to Today. A founder of the National History Center of the American Historical Association, he lives in Washington, D.C.
Print version record.
JSTOR
Keywords: Historiography; Historians; Historiographie; historiography; HISTORY / Historiography; Historians; Historiography